Safari [large type] - Hall, Parnell (Thorndike Press, 2015)
Stanley Hastings on safari? He didn't think so, until Alice's small inheritance -- plus scrimping on luxuries like food -- paid for a trip to Zambi. But the safari leader is a reckless, gung-ho, great white hunter, and a series of bizarre accidents dwindles the group's numbers. But were they really accidents? A stabbing tips the scale. It's murder, and the only policeman in a hundred miles is a park ranger. It's up to Stanley to crack the case.